Iron supplementation post-blood donation in Vietnam: Impact on hemoglobin, red cell indices, and iron reserves - Viet Pham Tuan; Son Dao Anh; Phong Hoang Van; Tuan Anh Bui Sy (Romanian Medical Journal)
Background. Regular blood donation plays a pivotal role in mitigating the formation of free radicals by regulating iron accumulation. However, frequent blood donation can lead to chronic iron deficiency. In this study, we aimed to evaluate the effectiveness of daily iron supplementation as an intervention to expedite hemoglobin (Hb) recovery among frequent blood donors at a hospital in Vietnam. Methodology. Conducted longitudinally within the Hematology Department of a Hanoi hospital from February to July 2023, our study involved 104 eligible participants. They received a daily iron supplement comprising 100 mg of elemental iron, 0.75 mg of folic acid, and 5 mg of zinc sulfate for a minimum of 8 weeks. Blood samples were collected at three key time points: before blood donation during recruitment, immediately after donation, and at least 8 weeks post-donation. Results. Our findings revealed moderate, statistically significant positive correlations between elemental iron administration and changes in platelet count (PLT), hematocrit (HCT), and mean corpuscular hemoglobin (MCH) (r = 0.753, p <0.001; r = 0.887, p <0.001; and r = 0.703, p <0.001, respectively). Additionally, weak but significant correlations were observed between elemental iron administration and red blood cell count (RBC), mean corpuscular volume (MCV), mean corpuscular hemoglobin concentration (MCHC), red cell distribution width coefficient of variation (RDWC), and red cell distribution width standard deviation (RDWS) (r = 0.260, p = 0.002; r = 0.302, p = 0.005; r = 0.160, p = 0.010; r = 0.120, p = 0.020; and r = 0.400, p <0.001, respectively). Conclusion. Over an eight-week duration, the regimen of daily iron supplementation yielded significant improvements in both red cell variables, red cell indices, and iron study variables, demonstrating its potential clinical impact.